2001
DOI: 10.1002/jsfa.945
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin inhibitor activity in vegetative tissue of sweet potato plants and its response to heat treatment

Abstract: Trypsin inhibitor activity (TIA) and crude protein content of seven genotypes of sweet potato were investigated. There was considerable genotypic variation in TIA, with a four-to ®vefold range in roots and a threefold range in stems. The mean TIA in stems at harvest time was 36% of that in roots, whilst the mean TIA in leaves was only 17% of that in roots. The TIA level in roots was correlated with that in stems (r = 0.83, p = 0.02) and leaves (r = 0.70, p = 0.08). In most genotypes the TIA level in vinetips w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
5
8
0
Order By: Relevance
“…However, in the hot-water fermentation, a 3.3%, 18.0% and 37.7% decrease in the mean TUI mL −1 was recorded on days 1, 2 and 3 respectively, compared to the initial value obtained on day 0 ( Table 5). These results are similar to those obtained in a previous study, 36 which showed that moist heating in a temperature controlled water bath at 60, 80 and 100 ∘ C for 15 min reduced trypsin inhibitor activity to 71%, 26% and 5% respectively of the original activities measured in fresh sweet potato roots. The decrease in level of trypsin inhibitor activity during hot-water fermentation may be due to the thermal sensitivity of the molecule.…”
Section: Discussionsupporting
confidence: 91%
“…However, in the hot-water fermentation, a 3.3%, 18.0% and 37.7% decrease in the mean TUI mL −1 was recorded on days 1, 2 and 3 respectively, compared to the initial value obtained on day 0 ( Table 5). These results are similar to those obtained in a previous study, 36 which showed that moist heating in a temperature controlled water bath at 60, 80 and 100 ∘ C for 15 min reduced trypsin inhibitor activity to 71%, 26% and 5% respectively of the original activities measured in fresh sweet potato roots. The decrease in level of trypsin inhibitor activity during hot-water fermentation may be due to the thermal sensitivity of the molecule.…”
Section: Discussionsupporting
confidence: 91%
“…Flouring after drying for 24 hr at 70°C is the most effective way to degrade the activity of trypsin inhibitors, followed by microwave baking. Higher temperatures led to further loss of trypsin inhibitor activity, with the activity completely lost after drying for 4 hr at 100°C, and moist heat treatment resulted in better inactivation of trypsin inhibitors than dry heat treatment (Sasi Kiran & Padmaja, ; Zhang & Corke, ).…”
Section: Discussionmentioning
confidence: 99%
“…Higher temperatures led to further loss of trypsin inhibitor activity, with the activity completely lost after drying for 4 hr at 100°C, and moist heat treatment resulted in better inactivation of trypsin inhibitors than dry heat treatment (Sasi Kiran & Padmaja, 2003;Zhang & Corke, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of CP were even higher in SPVL f ; however, the concentration declined 30% after drying. Zhang and Corke (2001) also noted that SP greens contained more protein than the roots and Van Soest (1994) stated that leaf proteins are mostly soluble cytoplasmic and chloroplast protein and therefore of higher value than root proteins. Cell wall proteins (extensions) are low in concentration.…”
Section: Statisticsmentioning
confidence: 99%
“…Traditional preservation methods such as air-drying, baking and powdering, cooking, steaming and fermentation change plant physiochemical properties, deactivate inhibitors (Yadang et al, 2013;Ahmed et al, 2010;Kirana and Padmaja, 2003) and inactivate spoilage enzymes. Senanayake et al (2013), Zhang and Corke (2001), and Lin (1989) confirmed that heating was effective against trypsin inhibitors; while Bradhury et al (1992), Colonna et al (1992) and Walter et al (1976) noted that heat increased hydrolysed starch to maltose increasing its digestibility. Processing, however, destroy carotenes, lowers amino acid, mostly lysine bioavailability and reducing sugars (Walter and Purcell, 1986) and affects antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%